2019
DOI: 10.1002/jcb.28829
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Baicalein retards proliferation and collagen deposition by activating p38MAPK‐JNK via microRNA‐29

Abstract: Immoderate proliferation and deposition of collagen generally result in hypertrophic scars and even keloids. microRNA‐29 (miR‐29) has been proved as a crucial regulator in these pathological processes. Although mounting evidence have proved baicalein (BAI) impairs scar formation, it is still incompletely understood whether miR‐29 participated in the underlying mechanism. In the present study, NIH‐3T3 cells were stimulated with BAI, and then cell viability was analyzed by cell counting kit‐8 (CCK‐8) and Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Baicalein decreased the expression level of miR-424-3p in lung cancer to suppress cell proliferation and improve cisplatin sensitivity (13). Baicalein activates p38-MAPK-JNK pathway via increasing the expression level of miR-29 to retard proliferation and collagen deposition (30). To date, few studies reported whether baicalein could alter several specific miRNAs expression pattern to further affect the progression of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalein decreased the expression level of miR-424-3p in lung cancer to suppress cell proliferation and improve cisplatin sensitivity (13). Baicalein activates p38-MAPK-JNK pathway via increasing the expression level of miR-29 to retard proliferation and collagen deposition (30). To date, few studies reported whether baicalein could alter several specific miRNAs expression pattern to further affect the progression of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have reported that baicalein exerted certain therapeutic effects on pulmonary brosis, hepatic brosis, cardiac brosis and renal interstitial brosis [8][9][10][11]. 150 µM baicalein suppressed TGF-β1induced collagen deposition as well as the expression of collagen I and α-SMA by activating p38MAPK/JNK pathway in NIH-3T3 cells [14]. Baicalein was also found to attenuate the production of type I collagen, downregulate expression of CTGF and α-SMA and retard α-SMA lament formation in TGF-β1-stimulated human lung broblasts [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that it has been increasingly used against pulmonary, hepatic, cardiac and renal brosis as potential therapeutic agents [8][9][10][11]. The suppression of brosis by baicalein was partially attributed to the attenuation of collagen and ECM production [12][13][14][15], inhibition of cell proliferation and induction of apoptosis of broblasts [16], inhibition of myo brolast differentiation [8] and downregulation of brogenic markers expression [9,13,14].Collectively, baicalein modulates pro-brotic and in ammatory pathways, then results in the inhibition of brosis in different organs. However, the effect of baicalein against SSc and the exact molecular mechanisms responsible for its effect have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt5a inhibited the induction of DFCs cellular senescence, supported cell proliferation and prevented cell death (59). Wnt5a significantly enhanced the proliferation of HPDLCs by phosphorylating two major mitogen-activated protein kinases, extracellular signal-regulated kinase and Jnk (27), which are important signaling molecules influencing cell proliferation (60). In addition, Wnt5a promoted the migration of HPDLCs by phosphorylating Akt, which serves pivotal roles in cell migration (61).…”
Section: Wnt5a In Periodontal Regenerationmentioning
confidence: 99%